Pyrolysis temperature optimization of biochar from tobacco stalk and its physicochemical characterization - YANG Xing; HUANG Huagang; WANG Ling; SHEN Yan; LU Kouping; HAN Xuebo; WANG Hailong (浙江大学学报. 农业与生命科学版)
Tobacco (Nicotiana tabacum L.) is an important commercial crop planted in China. Generally, tobacco stalks were burnt in the field after harvest, causing severe air pollution. The utilization of tobacco stalk has become an increasingly challenging issue in tobacco production, whereas conversion of tobacco stalk into biochar may provide a feasible approach. Biochar is a carbonaceous solid pyrolyzed from residual of agricultural and forest biomass. It can be used as soil amendment due to its favorable properties, such as high pH value, cation exchange capacity, oxygen-containing function groups, as well as microporous structures. Previous studies have demonstrated that biochar can be used for remediation of soils contaminated with organic and inorganic pollutants. Moreover, biochar has the potential of enhancing long-term sequestration on soil organic carbon, improving soil structure and water retention ability, promoting bioavailability and retention of the nutrients, and ultimately promoting plant growth and increasing crop yield. The environmental behavior and impacts of biochar mainly depend on its physical and chemical properties, while pyrolysis temperature is the main factor affecting the physicochemical characteristic.To understand the influence of pyrolysis temperature on the physicochemical properties of biochars, the tobacco stalk was pyrolyzed at 350,400,450,500,550 and 600 ℃, then the properties of biochars such as yield rate, pH value, electrical conductivity and specific surface area were determined. The composition and structure characteristics of biochars were investigated by scanning electron microscopy, Fourier transform infrared spectroscopy, energy dispersive X-ray spectrometry, X-ray diffraction and 13C-nuclear magnetic resonance analyses.The results showed that the yield rate, contents of O and H as well as the H/C, O/C, (O+N)/C ratios of the biochars decreased with the rise of pyrolysis temperature. However, the pH value, electrical conductivity, specific surface area and total carbon contents of biochars increased as the pyrolysis temperature increased. The yield rate and pH value of biochar tended to be stable above 500 ℃, and the specific surface area and pH value peaked at 450 ℃. With the rise of pyrolysis temperature, the content of mineral elements and surface crystal increased, whereas the content of oxygen-containing functional groups decreased. Concentrations of K, Al and Ca were 28.46-35.47,10.74-35.86 and 13.15-24.95 g/kg, respectively. The stability and aromaticity of biochar increased but its polarity decreased with the rise of pyrolysis temperature.Overall, the tobacco stalk biochar pyrolyzed at 450℃ could achieve the optimal benefits for agricultural production and environmental protection. The results can provide useful theoretical guidance and technological support for the recycle and utilization of tobacco stalk, and the application of tobacco stalk biochar in agricultural production and environmental protection.